PERFORMANCE APPRAISAL PRACTICES AS A TOOL TO IMPROVE EMPLOYEE EFFICIENCIES IN BANKING SECTOR - Nihar Ranjan Swain , Dr. Susanta Kumar Mishra (International Journal of Modern Agriculture, 2020)
The role of HR Manager in an Organization is many. One of the responsibilities of the HR Manager is the Performance Measurement. It is one of the important human management functions for any organization. Consequently, various tools and methods are used to measure the performance. Currently performance appraisal not only considers the rating technique of motivation but also stretched away from that. Measuring the performance is one of the most discussed topics in performance management. It is purely depend on environmental characteristics which help in achieving organizational objective. Notwithstanding anything employees’ job performance can control their way of doing any job. Additionally, this paper found that employees are interested to fulfil their personal objective effectively so as to not only can achieve their individual goal but also serve loyalty towards organizational objectives.